DEVELOPMENT OF RESOURCE-SAVING IRRIGATION TECHNOLOGIES FOR IRRIGATION OF COTTON FIELDS IN THE BUKHARA REGION, SAVING WATER RESOURCES USING HYDROGEL - Розиева Курсия Умаровна; Умурзакова Джахангира Шерали Сын; Мирзомуротов, Миршода Фархода сын (Scholars Digest Publishing, 2023)
In the cotton-growing countries of the world, on the basis of water- and resource-saving advanced technologies, the use of drip, rain and underground methods of irrigation of cotton and cotton-complex crops, scientific research is being carried out to achieve uniform moistening of the active layers of the system, to prevent high filtration, waste discharge into wastewater, reduce physical evaporation and save water and other resources during seasonal watering of crops. In It is important for the world to obtain a high and high-quality harvest from agricultural crops by improving new modern innovative water-saving technologies, it is important to develop advanced irrigation methods and widely use them in the face of global climate change.
Keywords: Resource, water, drip irrigation, cotton, quality crop.